DOI: 10.11606/t.22.2015.tde-08052015-145912
|View full text |Cite
|
Sign up to set email alerts
|

Condições de saúde de população negra remanescente de quilombo em Alcântara - MA

Abstract: É evidente que um projeto dessa natureza nunca seria desenvolvido sem o apoio de pessoas e instituições com as quais eu pude contar. O espaço é pequeno para agradecer a todos pelas contribuições, mas tentarei citar todos, a quem expresso meus agradecimentos.Agradeço primeiramente a Deus, por me possibilitar a realização desse sonho, pelas benções e presença em minha vida, me guiando e colocando pessoas maravilhosas no meu caminho.Aos meus pais, que sempre foram exemplo de bondade, caráter, honestidade e humild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Masonry houses in quilombola communities are not often found, many studies point to the predominance of mud or adobe houses (Bezerra et al, 2013;Cardoso et al, 2015;Araújo, 2017). In his research, Ferreira (2014), found an average of 4 to 5 rooms per house surveyed, however, this number is very variable, as Silva (2007) states, who found the presence of one to fourteen rooms in the residences surveyed.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Masonry houses in quilombola communities are not often found, many studies point to the predominance of mud or adobe houses (Bezerra et al, 2013;Cardoso et al, 2015;Araújo, 2017). In his research, Ferreira (2014), found an average of 4 to 5 rooms per house surveyed, however, this number is very variable, as Silva (2007) states, who found the presence of one to fourteen rooms in the residences surveyed.…”
Section: Resultsmentioning
confidence: 93%
“…), 55.21% of quilombola households do not have running water (Silva, 2015b). The lack of piped water supply that leads to the search for other inadequate sources adds to the poor conditioning of the liquid (Ferreira, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation